Household consumption expenditure in Thailand during the first COVID-19 lockdown - Oudom Hean; Nattanicha Chairassamee (Asia-Pacific Sustainable Development Journal, 2022)
The COVID-19 pandemic has been particularly challenging to developing countries, such as Thailand. Although the country has managed to control the outbreak relatively well, changes in the consumer spending behaviour could affect the whole economy. In this study, household consumption expenditure in Thailand during the first COVID-19 lockdown is examined by using descriptive and empirical analyses. The findings of this study indicate that total consumption declined drastically during the first two quarters of 2020. Consumer spending on services dropped significantly during that time, but spending on non-durable goods, durable goods and housing-related expenses increased. These expenditure patterns are similar to those in developed countries in which consumers increased their spending on at-home activities, but reduced their expenditures outside the home.